Addressing the elephant in the room: understanding functional neurological symptom disorder through the lens of culture and religion - Bokharey, Iram Zehra; Fahim, Urusa; Tahir, Khola; Shireen, Zarish (Frontiers in Neurology, 2023)
Owing to the dearth of scholarly works to understand the presence of Functional Neurological Symptom Disorder (FNSD) among mental health patients in Pakistan, this study sought to understand how cultural and religious conflicts are implicated in the aetiology of FNSD. The study recruited 22 participants, comprising five men and 17 women. The participants were recruited from the Department of Psychiatry at Services Hospital, Lahore, Pakistan. Semi-structured interviews were conducted and analyzed through Thematic Analysis. The two main themes identified in this study were cultural and religious values and beliefs about romantic relationships. Within the cultural and religious values theme, subthemes of self-perception, a conviction in religious beliefs, and sexual suppression were identified. Furthermore, the subthemes of beliefs about romantic relationships were family’s approval, engagement against wishes, and fear of exposure. The two main themes are interconnected: beliefs about romantic relationships were interpreted and experienced through the perspective of religion and culture. To summarize, this study concluded that stressors related to culture and religion are significant contributing factors in the development of FNSD. This study has important implications for mental health professionals, as awareness around the interplay of cultural as well as religious beliefs and FNSD will enable them to devise effective and holistic therapeutic intervention.